Diversity of hippoidean crabs - considering ontogeny, quantifiable morphology, and phenotypic plasticity - Braig,Florian (2021)
Abstract Representatives of Hippoidea, often called sand crabs or mole crabs, are an ingroup of Anomala. These marine crustaceans inhabit the tropical and subtropical coasts of the world, yet some also appear in temperate climates. Their adults are specialized for digging and living in sandy substrates. Hippoidean zoea-type larvae are planktic and reach large sizes up to a few centimetres. These larvae transform into megalopa larvae, strongly resembling the adult, mediating the transition to the benthic lifestyle of the adult. We reconstructed outlines in dorsal view of over 80 shields of hippoideans, including representatives of Blepharipodidae (sister group to all others), Albuneidae, and Hippidae and including adults, megalopa-type, and zoea-type larvae from all three ingroups. We conducted a morphological analysis on this data using an elliptic Fourier transformation and principal component analysis. We used the results of the analysis to discuss the life history of hippoideans and the special function of megalopae, which often lack emphasis in current research. Early stage zoea larvae, megalopae, and adults show a linear gradient in their morphological development according to our analysis. However, late stage zoea larvae deviate from this pattern, possibly due to their specialization to a long-lasting planktic life. Lastly, we discuss the influence of phenotypic plasticity in hippoidean zoea larvae.